Analisis Dan Perancangan Sistem Informasi Layanan Administrasi Kependudukan Berbasis Web Pada Kantor Lurah Pematang Sulur - Rosmalasari, Rosmalasari; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2021)
Kantor Lurah Sulur in population administration service still get trouble, such as: process requires services need time and money because must go to the office, information about population administration service only scattered with an ad and conversation society so that information not can spread quickly and precisely, and there is no website can give us claims to urban village office directly. The purpose of research is analyzing and design system information of population service web-based using PHP programming language and MySQL database. Metodology of this research use waterfall model and unified model language using use case diagram, activity diagram, and class diagram. Conclusion of this system can featuring population data, letter data, complaint data, information data that is structured and display report necessary. Research advice are prototyped this system should be devised well and properly so that it will could be applied to Kantor Lurah Sulur and next development can be added features to make report in graphic form